If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-24-8p=-8(3-5p)
We move all terms to the left:
-24-8p-(-8(3-5p))=0
We add all the numbers together, and all the variables
-8p-(-8(-5p+3))-24=0
We calculate terms in parentheses: -(-8(-5p+3)), so:We get rid of parentheses
-8(-5p+3)
We multiply parentheses
40p-24
Back to the equation:
-(40p-24)
-8p-40p+24-24=0
We add all the numbers together, and all the variables
-48p=0
p=0/-48
p=0
| 7.5x-2.2=5.3 | | X2-x=-840 | | -7x+7-6(x-1)=-6x-(6x-6)+6 | | 3(8x-3)=-6x+9 | | -10=7x-3x+7 | | 1/5–x/5=-3/5 | | 2+a*6=5 | | 14=5x+3 | | 2d2+31d–16=0 | | x/4=-1+x+3/5 | | 1/5y+1/4=2/5 | | -0.5(x+7)=0.9(4-x) | | 3.5x+25=7.5+17 | | 8(x-1)+3(x+5)=-15 | | 7+5m=26 | | x2+25x+24=0 | | 1=3x+1/2 | | 0=b^2-14b+47 | | -142.87=-9.1k | | 6-(3x+4)=2-3x | | -2(2a-7)=20-4a | | (2y-7)5-12y=3 | | 2m^2+27m-14=0 | | y-7/6=5/6 | | 8y-5y-10=46.76 | | 2=-2+a | | -8(x+1)-x-12=-9(x+5)+25 | | 0.10(y-2)+0.12y=0.02y-2 | | 2(x+1)=2x-(2-x) | | 13=6b+14 | | 108=4n | | 23u^2+45u-2=0 |